Risk factors of low bone mass in young patients with transfusion-dependent beta-thalassemia - Zhang, Wei; Liu, Rongrong; He, Siping; Huang, Jihua; Wu, Liting; Huang, Cuifeng; Liang, Yuzhen; Lai, Yongrong (Frontiers in Endocrinology, 2025)
ObjectiveTo determine the prevalence of low bone mass and associated risk factors among children and adolescents suffering from transfusion-dependent beta-thalassemia (TDT).MethodsIn this study, a total of 389 children and adolescents with TDT (236 males and 153 females), treated between January 2015 and December 2024 in the Department of Hematology at the First Affiliated Hospital of Guangxi Medical University, were selected. Subjects were categorized into those with normal bone mass and those with low bone mass based on bone mineral density assessments. Comparative analyses of various indicators between these two groups were performed.ResultsThe overall prevalence of low bone mass in TDT patients aged 2–19 years without height-adjusted bone mineral density(BMD)correction was 31.6%, with a prevalence of 33.4% in the 5-19-year subgroup. Multivariate analysis identified age (OR = 1.149, 95% CI 1.052–1.256, P < 0.05), IGF-1 levels < -2 SD (OR = 1.832, 95% CI 1.095–3.067, P < 0.05), and hypogonadism (OR = 2.990, 95% CI 1.087–8.229, P < 0.05) as independent risk factors for low bone mass. After applying height-adjusted BMD correction to the 5-19-year subgroup, the prevalence of low bone mass decreased to 15.8%. In this subgroup, multivariate analysis revealed age (OR = 1.137, 95% CI: 1.034–1.251, P < 0.05), normal BMI (OR = 0.383, 95% CI: 0.158–0.976, P < 0.05), and albumin (ALB) levels (OR = 0.866, 95% CI: 0.783–0.953, P < 0.05) as independent predictors of low bone mass.ConclusionThis study reveals a high prevalence of low bone mass in children and adolescents with TDT. Without height-adjusted BMD correction, the overall prevalence was 31.6% (33.4% in the 5-19-year subgroup), which significantly decreased to 15.8% in the 5-19-year subgroup after height-adjusted correction, highlighting that traditional BMD assessments may overestimate risk due to unaccounted short stature. Multivariate analysis demonstrated that advancing age consistently remained an independent risk factor (pre-correction OR=1.149; post-correction OR=1.137). The corrected model further identified normal BMI (OR=0.383) and ALB (OR=0.866) as protective factors, while IGF-1 levels < -2 SD (OR=1.832) and hypogonadism (OR=2.990) emerged as significant risks in the uncorrected model. Clinical management should prioritize height-adjusted BMD evaluation and integrated interventions targeting growth hormone axis function, gonadal status, and nutritional indicators to optimize bone health in TDT patients.